Synthesis, biophysical properties, and nuclease resistance properties of mixed backbone oligodeoxynucleotides containing cationic internucleoside guanidinium linkages: Deoxynucleic guanidine/DNA chimeras - Barawkar, Dinesh A. (The National Academy of Sciences, 1998)
The synthesis of mixed backbone oligodeoxynucleotides (18-mers) consisting of positively charged guanidinium linkages along with negatively charged phosphodiester linkages is carried out. The use of a base labile-protecting group for guanidinium linkage offers a synthetic strategy similar to standard oligonucleotide synthesis. The nuclease resistance of the oligodeoxyribonucleotides capped with guanidinium linkages at 5′ and 3′ ends are reported. The hybridization properties and sequence specificity of binding of these deoxynucleic guanidine/DNA chimeras with complementary DNA or RNA are described.